The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1413-35552006000300002
|View full text |Cite
|
Sign up to set email alerts
|

Issues in aging in individuals with life long disabilities

Abstract: Introduction: The major research data and findings related to aging among persons with developmental disabilities are discussed. Topics addressed include prevalence and mortality rates, as well as the effects of aging on the sensory systems, the neuromusculoskeletal system and the cardiopulmonary system. The discussion also focuses on the clinical implications of these changes among aging individuals with developmental disabilities. Conclusion: Although the individual needs of persons with developmental disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…This is likely due to osteoarthritis and shortened cervical muscles, which, according to Connolly (2006), can occur frequently with the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to osteoarthritis and shortened cervical muscles, which, according to Connolly (2006), can occur frequently with the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…To reach adequate statistical power ( β = 0.80), this model required at least 52 participants. We did not include age as a covariate in the initial three‐group statistical model as the onset of aging effects occurs earlier in adults with intellectual disabilities, including PWS, compared with healthy adults (Connolly 2006; Lin, Wu, Lin, Lin & Chu 2011; Mimi, Kwan & Lau 2018).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that people with intellectual disability experience aged related changes from the third decade in life (Connolly, ; Coppus, ); therefore, participants in the larger cohort study were adults with intellectual disability aged 35 and over. Those participants who fell in the first phase of the study were purposefully sampled and recruited for the follow‐up interviews.…”
Section: Methodsmentioning
confidence: 99%